4x2-4x-3=0 can be written as (2x-3)(2x+1)=0
Anything times by 0 equals 0 ( the zero property of multiplication) therefore we need to make each one of these terms in brackets equal to 0.
so 2x-3=0 giving x=3/2
and 2x+1=0 giving x=-1/2
That doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (-7 plus or minus i times the square root of 23) divided by -3x = 2.3333333333333335 + -1.5986105077709063ix = 2.3333333333333335 - -1.5986105077709063iwhere i is the square root of negative 1
That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: 3 plus or minus -1.75 times the square root of 3 t = -0.0310889132455352 t = 6.0310889132455352
-(h - 4)(h + 8)
(x + 5)(x + 5)
Remember to factor out the GCF of the coefficients if there is one. A perfect square binomial will always follow the pattern a squared plus or minus 2ab plus b squared. If it's plus 2ab, that factors to (a + b)(a + b) If it's minus 2ab, that factors to (a - b)(a - b)
24
100 equales
It doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: 7 plus or minus i times the square root of 47b = 7 + 6.855654600401044ib = 7 - 6.855654600401044iwhere i is the square root of -1
25x (square) plus 40 plus 15 equals 680.
(a + 2b)(a + 2b)
That equals 1.25x. There's nothing to factor.
If you mean: -3-10x = 25+4x then the value of x works out as -2
It cannot be factored.
2 + tansquareA + cossquareA
168
2 and 3
You can always add radicals, but you can't simplify unless the radicands have a common factor. For example, the square root of 20 plus the square root of 45 equals 2 times the square root of 5 plus 3 times the square root of 5, which is 5 times the square root of 5.